Angel cat - Garland, Michael, 1952- (Honesdale, Pa. : Boyds Mills Press, 1998)
A cat returns from heaven to rescue her owners.
Kirkus Review.
L.A. Recommended Foreign Language.
4.2
K-3
Keywords: Cats -- Fiction; Angels -- Fiction; Cats -- Fiction; Angels -- Fiction; Fires -- Fiction; Cats -- Fiction; Death -- Fiction; Pets -- Fiction; Angels -- Fiction